What is putting brakes on economy’s growth engine? : A select study on MSMEs in India - Bhardwaj, Shivam; Kaushal, Arun; Singh, Himani; Saxena, Ankit; Dwivedi, Ram Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Micro Small and Medium Enterprise (MSME) sector in India is one of the crucial contributors to overall economic development. It acts as one the major supporter to any government looking for the overall economic development either of the state or of the country. Employment generation, use of local resources and traditional or inherited skills, low capital and technological requirements, mobilization of resources etc. are few key reasons highlighting the significance of this sector. However it is not so easy to start a business and to sustain in the market, specifically when we are talking about developing country like India, even if when there are numerous efforts being made by the government towards the development and prosperity of MSME sector. This paper is based on a survey carried out in 123 Indian MSMEs to investigate the problems faced by them that affect their performance, so that the same could be taken into consideration by the policymakers for effective planning, decision making, and structured implementation. This study revealed, in ranking order, various problems or challenges being faced by the enterprises related to finance, management, raw material technology, marketing, etc. Results of the study show that when it comes to the problems being faced by various MSME’s, except finance they are almost similar irrespective of the nature of the organization.